Internalisasi Nilai Kedisiplinan melalui Metode Pembiasaan dalam Upacara Bendera Siswa Kelas V SDN 34 Rejang Lebong - Viola, Octa; Lusa, Herman; Susanti, Atika (Universitas Bengkulu, 2025)
The purpose of this study is to describe the implementation of internalization of student discipline values through habituation methods in flag ceremony activities This research is a descriptive research with a qualitative type of research. The subjects of this study were 5th grade teachers and students. The data collection techniques used were observation, interviews, and documentation. The credibility of the data used, namely triangulation and member check. Data analysis is carried out through data collection, data condensation, data presentation and conclusions. The result of this study is that there are three stages of value internalization, namely value transformation, value transactions and value trans- internalization and in ceremonial activities there are 10 indicators. The conclusion of this study is that the three stages in internalizing the value of discipline in flag ceremony activities have been shown by students even though they have not fully demonstrated the attitude of 5th grade students. Indicators that are still not shown by students are not following the reading of Pancasila, not using fully clothed attributes such as ties and belts, students also do not disperse ranks regularly when the flag ceremony is over.